Lacorte, Manel, y Agustín Reyes-Torres. Didáctica del español como 2/L en el siglo XXI. Madrid: Arco/Libros, 2021. 344 pp. (ISBN: 978-84-7133-850-1) (Rilce. Revista de Filología Hispánica, 2024)
Book Review